Предмет: Алгебра,
автор: ArTeM1404228
3/7×y - 13 = - 12 + y/7 (Знайти y)
Ответы
Автор ответа:
1
3/7 · у - 13 = - 12 + у/7
3/7 · у - 13 = - 12 + 1/7 · у
(3/7 - 1/7) · у = 13 - 12
2/7 · у = 1
у = 1 : 2/7
у = 1 · 7/2
у = 3 1/2 (или 3,5 в десятичных дробях)
-----------------------------------------------------------
Проверка: 3/7 · 7/2 - 13 = - 12 + 7/2 : 7
3/2 - 13 = - 12 + 7/2 · 1/7
1 1/2 - 13 = - 12 + 1/2
- 11 1/2 = - 11 1/2
Похожие вопросы
Предмет: Геометрия,
автор: Airat105
Предмет: Русский язык,
автор: АняМалик
Предмет: Биология,
автор: olya1597
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: Красавица3683